Prevenção de lesão por pressão no contexto hospitalar: uma revisão sistemática - VESTEMBERG, Cristielen Valadares (2023)
Introduction: The use of adaptations for positioning in bed is relevant in the hospitalization process, which among them are the support surfaces, as they have the objective of relieving and/or redistributing the pressure in the body. Objective: Identify and analyze scientific evidence about the effectiveness of support surfaces in preventing pressure injuries in hospitalized patients. Method: This study is a systematic quantitative review based on the PRISMA guidelines. Searches were performed in the Cochrane Library, OTSeeker, PubMed and Embase databases, using the following combination of terms: ‘‘Support surface’’ OR Mattresses AND ‘‘Pressure Ulcer’’ OR Bedsore OR ‘’Pressure Sore’’ OR ‘‘Decubitus ulcer’’ AND Hospital OR Hospitals. Texts in English published between 2013 and 2022 were included. Two researchers performed the literature searches and independently extracted data from the studies and the concordance was submitted to Kappa analysis. The level of evidence and methodological quality of the included studies were assessed using the PEDro scale and the Cochrane risk of bias tool, respectively. Results: Studies evaluated alternating pressure air support surfaces, reactive air, foam, motorized, gel and water . It was highlighted that the devices have uncertain effectiveness in preventing pressure injury (PI). Conclusion: Alternating pressure air surfaces and foam surfaces showed significant results in decreasing injury in critically ill patients, that future studies may carry out a priority assessment and guide professionals to make current clinical recommendations and assist in the development of new types of devices.